Host‐Microbial Cometabolite Ursodeoxycholic Acid Protects Against Poststroke Cognitive Impairment - Xuxuan Gao; Feng Zhang; Jiafeng Zhang; Yu Ma; Yiting Deng; Jiaying Chen; Yueran Ren; Huidi Wang; Boxin Zhao; Yan He; Jia Yin (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Poststroke cognitive impairment (PSCI) is a common residual disability after stroke, often underestimated and underdiagnosed. We previously found that ursodeoxycholic acid (UDCA), a host‐microbiota cometabolite, ameliorates brain damage in stroke mice. Based on these findings, we aimed to evaluate the predictive value of UDCA for PSCI risk in a prospective cohort study. Methods and Results We recruited 202 patients with mild acute ischemic stroke and 63 patients with symptomatic large‐artery atherosclerotic stenosis as the modeling and external validation cohorts, respectively. Mice were subjected to transient middle cerebral artery occlusion, and cognitive function was assessed using the Morris water maze test. Patients with mild acute ischemic stroke who developed PSCI exhibited significant alterations in gut microbiota and plasma bile acid profiles during the acute stroke phase, including a notable reduction in UDCA level. Through feature selection and machine learning, we constructed a predictive model for PSCI incorporating plasma UDCA level, the relative abundance of Clostridia, Bacilli, and Bacteroides, as well as age, educational level, and the presence of moderate to severe white matter lesions. This model exhibited robust predictive performance in both internal (area under the curve, 0.904 [95% CI, 0.808–1.000]) and external (area under the curve, 0.838 [95% CI, 0.742–0.934]) validations. Animal studies in mice also showed reduced UDCA levels in plasma and brain tissue following stroke. UDCA administration improved cognitive function in stroke mice by reducing hippocampal microglial activation and neuronal apoptosis. Conclusions Our findings indicate that UDCA has potential as a biomarker for predicting PSCI risk and plays a neuroprotective role in the progression of PSCI. This suggests that early identification and intervention targeting UDCA could represent a promising strategy for the prevention and treatment of PSCI.